Optimization of temperature coefficient of resistance of Al-doped vanadium oxide thin film prepared by atomic layer deposition for uncooled microbolometer. Issue 11 (1st June 2022) - Shin, Heecheol; Duy, Le Thai; Seo, Hyungtak
Abstract: Vanadium oxide (VOX ) is an excellent thermal sensitive candidate for uncooled microbolometers. However, undoped VOX prepared by atomic layer deposition (ALD) has a temperature coefficient of resistance (TCR) of ca. −2 ∼ −3%/K. For improving its TCR, our deposition approach based on the combination of ALD and rapid post-deposition annealing (RTA) is proposed. Besides, aluminum-doping into the VOX films is performed via that approach, and the number of Al2 O3 cycles is adjusted for varying the dopant loadings. Changes in physical, chemical, and electrical characteristics of the VOX films due to Al-doping are discussed in detail. The advantage of introducing Al 3+ dopants is to hinder the thermally activated phase transition of VO2 phases, leading to an improvement in TCR of Al-doped VOX up to −4.2%/K, which remains stable over a wide temperature range of 298–328 K. However, the excessive Al doping also carries an adverse effect on TCR. The reason for that is discussed for further understandings of doping effects.